The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/maec.12052
|View full text |Cite
|
Sign up to set email alerts
|

Infaunal macrobenthos of the oxygen minimum zone on the Indian western continental shelf

Abstract: The Arabian Sea is characterized by a mid-depth layer of reduced dissolved oxygen (DO) concentration or oxygen minimum zone (OMZ -DO concentration <0.5 mlÁl À1 ) at~150-1000 m depth. This OMZ results from the flux of labile organic matter coupled with limited intermediate depth water ventilation. Generally, benthic animals in the OMZ have morphological and physiological adaptations that maximize oxygen uptake in the limited oxygen availability. Characteristics of OMZ benthos have been described from only a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…In the present study the second dominant group was crustaceans, as found in previous works (Jayaraj et al 2007;Joydas & Damodaran 2009, 2013Musale & Desai 2011) and in other areas (Johnson et al 2007;Sellanes et al 2007;Mamouridis et al 2011;Naser 2011). Hoey et al (2004 reported 65 species (34%) of crustaceans, which constituted the second most dominant group among macrobenthos.…”
Section: Compositionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study the second dominant group was crustaceans, as found in previous works (Jayaraj et al 2007;Joydas & Damodaran 2009, 2013Musale & Desai 2011) and in other areas (Johnson et al 2007;Sellanes et al 2007;Mamouridis et al 2011;Naser 2011). Hoey et al (2004 reported 65 species (34%) of crustaceans, which constituted the second most dominant group among macrobenthos.…”
Section: Compositionsupporting
confidence: 90%
“…Joydas & Damodaran (2009) also observed the dominance of polychaetes (56.97%) in the macrofauna of the west coast of India, followed by crustaceans (28.05%). The dominance of polychaetes in the shelf region of the India has been reported by various workers (Vizakat et al 1991;Prabhu et al 1993;Ganesh 2003;: Jayaraj et al 2007;Ganesh & Raman 2007;Joydas & Damodaran 2013).…”
Section: Compositionmentioning
confidence: 55%
See 1 more Smart Citation
“…On the west coast of India, sediment organic matter levels were appreciably higher within the OMZ areas, coinciding with depleted DO (Ingole et al . ; Joydas & Damodaran ). Our observations in the Bay of Bengal are in conformity with the generalised models – falling DO levels coincided with depths that promoted organic matter accumulation within the OMZ.…”
Section: Discussionmentioning
confidence: 99%
“…The recently concluded Deep Gulf of Mexico Benthos program on the continental slope and abyssal plain of Mexico is one example of a program aimed at understanding how oil and gas exploration and production might affect the ecosystem and its inhabitants even at such great depths (Rowe & Kennicutt 2008). In the Indian Ocean region, deep-sea macrobenthos investigations in relation to the OMZ have been carried out on the Oman margin in the NW Arabian Sea (Levin et al 2000) and more recently on the Pakistan slope Hughes et al 2009;Levin et al 2009b;Murty et al 2009) and the West Indian shelf in the Arabian Sea Hunter et al 2011Hunter et al , 2012Levin et al 2013;Joydas & Damodaran 2014). At present, macrobenthic studies on the E Indian margin in the Bay of Bengal are limited to mid-shelf depths (30-200 m;Ganesh & Raman 2007).…”
Section: Introductionmentioning
confidence: 99%